1995
DOI: 10.1007/bf00328905
|View full text |Cite
|
Sign up to set email alerts
|

Energy allocation for reproduction in a marsupial arboreal folivore, the common ringtail possum (Pseudocheirus peregrinus)

Abstract: This study examines the annual energetics of a small folivorous marsupial, Pseudocheirus peregrinus. Particular attention was given to the energy and time allocated to reproduction by the females. Daily energy expenditure was measured directly using the doubly labelled water technique. Energy transferred to the young via the milk was estimated from information on milk composition and production. There was no significant seasonal variation in the energy expenditure or water influx of males or females. The mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Nagy & Suckling (1985) observed no difference between the metabolic rates of non-lactating and lactating female sugar gliders with one and two young, all estimated to be only a few weeks old. These results are in agreement with several other mammals studied during pregnancy and lactation, in which additional energetic costs for the mother were observed only in the latter half of lactation (Kenagy, Sharbaugh & Nagy, 1989;Munks & Green, 1995;Green, Merchant & Newgrain, 1997). This pattern of energetic cost to the mother during lactation can be explained by the rates of energy consumption of the developing young.…”
Section: Discussionsupporting
confidence: 92%
“…Nagy & Suckling (1985) observed no difference between the metabolic rates of non-lactating and lactating female sugar gliders with one and two young, all estimated to be only a few weeks old. These results are in agreement with several other mammals studied during pregnancy and lactation, in which additional energetic costs for the mother were observed only in the latter half of lactation (Kenagy, Sharbaugh & Nagy, 1989;Munks & Green, 1995;Green, Merchant & Newgrain, 1997). This pattern of energetic cost to the mother during lactation can be explained by the rates of energy consumption of the developing young.…”
Section: Discussionsupporting
confidence: 92%
“…Preliminary support for this idea comes from Krockenberger and colleagues (1998), who suggested that the low daily production and low protein/lipid content of female koala milk is an adaptation to the low protein/lipid content of their specialized diet of Eucalyptus foliage. Similar reductions in maternal investment in lactation appear in other folivorous marsupials (Munks and Green 1995), but more work is needed to consider this hypothesis within a broader phylogenetic context.…”
Section: Parental Investmentmentioning
confidence: 87%
“…Observations of water flux in wild Pseudocheirids indicate that all rely on free water to meet part of their water requirements (Foley et al 1990;Goudberg 1990;Munks and Green 1995). This is also likely to be true for P. archeri.…”
Section: Water Intake Requirements Of Rainforest Ringtail Possumsmentioning
confidence: 91%
“…An average-sized individual (1,170 g) P. archeri is predicted to require 172 ml d -1 of water (Nagy and Bradshaw 2000). To satisfy predicted water requirements from foliage alone, an average-sized individual of P. archeri would have to consume 65-82 g d -1 DW foliage (assuming a water content of 65-70% for preferred foliage : Goudberg 1990;Jones and Krockenberger, unpublished data; and 20 ml d -1 metabolic water production: Munks and Green 1995;Foley et al 1990). Adjusted for mass this is up to 70% higher than intake rates for other pseudocheirids (Foley et al 1990;Marsh et al 2003b), and may not be feasible.…”
Section: Water Intake Requirements Of Rainforest Ringtail Possumsmentioning
confidence: 99%
See 1 more Smart Citation